Autofluorescence bronchoscopy with white light bronchoscopy compared with white light bronchoscopy alone for the detection of precancerous lesions: a European randomised controlled multicentre trial. Issue 6 (27th May 2005) - Häußinger, K; Becker, H; Stanzel, F; Kreuzer, A; Schmidt, B; Strausz, J; Cavaliere, S; Herth, F; Kohlhäufl, M; Müller, K-M; Huber, R-M; Pichlmeier, U; et al.
Abstract : Background: The potential of autofluorescence bronchoscopy (AFB) to detect precancerous lesions in the central airways and its role in lung cancer screening is uncertain. A study was undertaken to evaluate the prevalence of moderate/severe dysplasia (dysplasia II–III) and carcinoma in situ (CIS) using a newly developed AFB system in comparison with conventional white light bronchoscopy (WLB) alone. Methods: In a prospective randomised multicentre trial, smokers ⩾40 years of age (⩾20 pack-years) were stratified into four different risk groups and investigated with either WLB+AFB (arm A) or WLB alone (arm B). Results: 1173 patients (916 men) of mean age 58.7 years were included. Overall (arms A and B), preinvasive lesions (dysplasia II–III and CIS) were detected in 3.9% of the patients. The prevalence of patients with preinvasive lesions in the WLB arm was 2.7% compared with 5.1% in the WLB+AFB arm (p = 0.037). For patients with dysplasia II–III, WLB+AFB increased the detection rate by a factor of 2.1 (p = 0.03), while for CIS the factor was only 1.24 (p = 0.75). The biopsy based sensitivity of WLB alone and WLB+AFB for detecting dysplasia II–III and CIS was 57.9% compared with 82.3% (1.42-fold increase). The corresponding specificity was 62.1% compared with 58.4% (0.94-fold decrease). Conclusions: This first randomised study of AFB showed that the combination of WLB+AFB was significantly superior to WLB alone in detecting preneoplastic lesions. Our findings do not support the general use of AFB as a screening tool for lung cancer, but suggest that it may be of use in certain groups. The precise indications await further study.